Augmented reality in the teaching of geometric solids for elementary school: Experience report in a public school - Paulo Vitor da Silva Santiago; Umy Zahroh; Rani Darmayanti (CV. FOUNDAE, 2023)
Background: Augmented Reality (AR) integrates virtual objects with the real world on smartphone screens, creating a seemingly seamless blend of both.Aim: This research aimed to explore the use of AR in teaching geometric solids to final-year elementary school students. An interactive tool, RA Solids, was employed, originating from a 2023 research experience in a 6th-grade class.Method: The study was conducted in a public school with students mostly classified as digital immigrants. The Didactic Engineering methodology was utilized for research.Result: The outcomes were positive, showing that the school environment was conducive to implementing the teaching and learning process of geometric solids using digital technology.Conclusion: The use of AR in education, specifically in teaching mathematics, demonstrates promising results in enhancing student engagement and understanding, particularly in the context of geometric solids.